PROFESSIONAL COMPETENCIES OF FINE ARTS TEACHERS IN HIGHER EDUCATION AND THEIR INFLUENCE ON STUDENTS (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the formation of professional competencies for a fine arts teacher in the higher education system and their impact on students. The concept of professional competence is analyzed from pedagogical and artistic perspectives, and the theoretical and practical aspects of competence development based on teacher-student interaction are substantiated. The research results showed that a teacher's professional and methodological potential directly influences students' creative activity, motivation, and educational effectiveness. In conclusion, recommendations were provided aimed at improving the professional competence of fine arts teachers in higher education institutions.
Keywords: Professional competence, fine arts, higher education, student, art history, creativity, pedagogical mastery, aesthetic taste, technical skills, innovative technology.